Air embolism in ventilated very low birthweight infants. Issue 5 (May 1988) - Fenton, T R; Bennett, S; McIntosh, N
Abstract : Five cases of air embolism in ventilated very low birthweight infants are reported. In all cases the outcome was fatal with the babies dying at about 15 hours of age.